A qualitative method in identifying academic aspect element of academic enhancement support for student-athlete - Rozali, Mohd Zulfadli; Puteh, Saifullizam; Yunus, Faizal Amin Nur; Azizuddin Khan, Thariq Khan (Hampstead Psychological Associates, 2020)
Student-athletes who are enrolled at the undergraduate level in higher educational institutions in Malaysia have the challenge of raising their academic achievement. Preliminary survey shows that nearly 40 percent of student-athletes have cumulative grade point average (CGPA) below 3.00. This study aimed to develop an academic enhancement support framework for student-athletes in Malaysian Public Universities. Problems, in order to improve academic achievement among student-athletes, are due to factors of academic factor that do not support the improvement of academic achievement student-athletes during their study sessions. As a result, student-athletes could not be maintained in the session of study, scholarship, and the implications from the result are they are not allowed to participate in training and also competition. Therefore, the purpose of this study was to explore elements of support increase academic achievement to students-athletes in aspects of academic. Qualitative research approach involves 12 respondents representing academia, management institutions and the management of student-athletes to explore elements of support increase academic achievement in terms of academic area for student-athletes. This data is collected through face to face interview and data analyzed based on thematic analysis by using pencil and paper to identify elements of support increase academic achievement in aspects of academic area. The result of the analysis found that there are 10 elements in aspects of academic area that can help increase the academic achievement of student-athletes that enroll undergraduate programs in Malaysia Public Universities. Therefore, 10 elements of support expected to help undergraduate student-athletes at public universities to improve their academic achievement.